Nail Matrix Pathology in Cronkhite–Canada Syndrome: The First Case Report. (November 2017) - Chuamanochan, Mati; Tovanabutra, Napatra; Mahanupab, Pongsak; Kongkarnka, Sarawut; Chiewchanvit, Siri
Abstract : Abstract: Cronkhite–Canada Syndrome (CCS) presents with gastrointestinal polyposis and the triad of cutaneous abnormalities including nail dystrophy, alopecia, and hyperpigmentation of the skin. The etiology is not well understood. The histology of skin lesion in CCS has not been routinely described. Especially, the nail matrix pathology has not been reported. In this study, the authors report the nail matrix pathology in a patient with CCS. Interestingly, the histologic evaluation revealed matrix hypergranulosis. Because matrix hypergranulosis is commonly found in several inflammatory nail diseases, this discovery points out that an inflammatory process is probably one of the important pathogeneses in CCS.